Answer:
C) -1
Explanation:
we have the following functions:
![f(x)=x-4](https://img.qammunity.org/2021/formulas/mathematics/high-school/q5d84qn4907wz7av242rc61jusftfqx7k9.png)
and
![g(x)=-2x-7](https://img.qammunity.org/2021/formulas/mathematics/middle-school/mpyeufatr0r29oocmcocba576y06plztp8.png)
to find the solution of
![f(x) = g(x)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/wqzwxh4odtu32tppzn5v5zphci5c1142sk.png)
what you need to do is to match the two functions:
![f(x) = g(x)\\x-4=-2x-7](https://img.qammunity.org/2021/formulas/mathematics/middle-school/qtqkbw2w1s6yanw27n8g50yki6mz00gbgs.png)
and now we solve this equation for x.
we move the -2x to the left as a +2x, and the -4 on to the right as a +4
:
and we add the quantities on both sides:
![3x=-3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/835ffkjojwavhpczwat89mpdjn7c6003a0.png)
dividing by 3:
![x=-3/3\\\\x=-1](https://img.qammunity.org/2021/formulas/mathematics/middle-school/mo7xeoxaojfxldx56guixtpqrbz7zz1e30.png)
the solution to the equation is
C) -1